Batch Sizing and Lot Splitting Strategies to Reduce Cycle Time in Semiconductor Assembly Process - Zakiyah Zain; Siti Mariam Man; Mohd Kamal Mohd Nawawi (International Journal of Supply Chain Management, 2020)
Increasingly, products with customized features are manufactured in small batches based on demand by unique customers. Such diversity leads to high product mix, thus severely impacting both production planning and scheduling activities such as frequent equipment setup and conversion. Despite increased complexity, production continues being pressured on minimal cycle time to meet on-time delivery requirements. Focusing on the most challenging process, which is assembly, this paper presents batch sizing and lot splitting strategies to improve production cycle times. In the event of too short cycle time, overlapping technique is the most applicable, while “parallel” technique applies to normal cycle time. The commonly known “batch queue” technique works well for long cycle time such as new product qualification lot.